MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK - Hendrik Pantas; Krista Surbakti (Universitas Quality, 2020)
ABSTRACTEducation does not necessarily greatly affect learning outcomes and Closed education: students, educators, materials, models / methods, curriculum, learning facilities and infrastructure. Educators are people who are responsible for the implementation of education targeting students. Student trainees improve their education in three environments, namely the Family Environment, School Environment, and Community Environment. Therefore, those responsible for education are parents, teachers, leaders in the learning, training and community programs. However, so far there is still something found in the learning process carried out. Therefore to solve this problem actions will be chosen using the Talking Stick Model because by using the Talking Stick model, the student acceptance process will be more memorable about making agreements by making good. Students will also be more active and interested in participating in learning because they are directly involved in learning a kensep through stick games by the teacher and students themselves in the classroom.